A Fault-Tolerant Control Approach Based on Image Processing Applied to Three-Tank System - Ali Abdo (IEEE, 2021)
This paper presents an innovative and practical solution for fault-tolerant control of industrial systems based on hybrid redundant measurements. The paper proposes a fault-tolerant control scheme against single and multiple sensor faults that can occur in typical tank-based industrial applications. A robust fault detection filter based on $H_{-} /H_{∞ }$ index is designed to generate a residual signal that is robust against disturbance and sensitive to the fault, simultaneously. It also integrates camera information and image processing techniques in the control scheme to get level-measurement redundancy. The proposed scheme was tested using the well-known three-tank benchmark, with both offline and online computation. Results showed that the proposed scheme tolerated the sensor faults and preserved the correct operation of the tank levels in both single and multiple-sensor faults, without changing the original structure of the controller.